A Perovskite Electrocatalyst for Efficient Hydrogen Evolution Reaction. Issue 30 (17th May 2016) - Xu, Xiaomin; Chen, Yubo; Zhou, Wei; Zhu, Zhonghua; Su, Chao; Liu, Meilin; Shao, Zongping
Abstract : Perovskite oxides are demonstrated for the first time as efficient electrocatalysts for the hydrogen evolution reaction (HER) in alkaline solutions. A‐site praseodymium‐doped Pr0.5 (Ba0.5 Sr0.5 )0.5 Co0.8 Fe0.2 O3– δ (Pr0.5BSCF) exhibits dramatically enhanced HER activity and stability compared to Ba0.5 Sr0.5 Co0.8 Fe0.2 O3– δ (BSCF), superior to many well‐developed bulk/nanosized nonprecious electrocatalysts. The improved HER performance originates from the modified surface electronic structures and properties of Pr0.5BSCF induced by the Pr‐doping.